Analisis Satua I Ubuh dengan Satua Bagus Diarsa (Teks Perbandingan) - Ayu Desi Yanti, Ni Putu; Suteja, I Wayan; Suryati, Ni Made (Humanis, 2018)
This study discussed two literary works of oral prose namely I Ubuh story and Bagus Diarsa story, which aims at understanding and investigating the existence of a text in another text or the intertextual relation in the story of I Ubuh and Bagus Diarsa. This study is conducted based on the structural theory from Teeuw and intertext theory from Kristeva, while the data collection is done by using free guided interview and supported by recording technique, taking notes, transcription and translation techniques. The methods used in analyzing the data are qualitative method and descriptive analytic method. In presenting the data analysis, the method used is informal method supported by deductive and inductive techniques. The findings of this study show that there are structures which form the story of I Ubuh and Bagus Diarsa namely incident; chronological plot in the stories; characters and characterizations such as main character, secondary figures, and complementary characters; the settings of both stories are setting of time, place and situation; the theme of the stories is Satya Samaya; and the moral. Besides, the findings show that there is intertextual relation between the story of I Ubuh and Bagus Diarsa, they have the similar motives namely chicken feathers that used to show directions and places in the stories. Meanwhile, the difference between these stories is I Santeng went southeast to reach the sea floor, and I Bagus Diarsa went north to reach the Banyan Tree.